Development of Contextual-Based Digital Comic Media to Improve Numeracy Skills of Grade II Elementary School Students - Siti Nur Adhinda (Sains Global Institut, Indonesia, 2026)
Numeracy skills are fundamental competencies that constitute a primary demand in 21st-century education, particularly for elementary school students. The low level of students' ability to solve mathematical word problems remains an urgent issue that needs to be addressed through more contextual and engaging learning media innovations. This study aims to develop contextual-based digital comic media to improve the numeracy skills of Grade II elementary school students. The research employed a Research and Development (R&D) method using the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). The participants consisted of 28 Grade II students from SDN Makassar 1. Research instruments included expert validation sheets, student response questionnaires, observation sheets, and pretest-posttest instruments. The validation results showed scores of 87.5% from the material expert, 84.2% from the media expert, and 89.0% from the language expert, all categorized as highly valid. The practicality level of the media reached 88.3%. The effectiveness of the media was demonstrated by an increase in the average score from 58.6 in the pretest to 82.4 in the posttest, with an N-Gain score of 0.57 (moderate category). Therefore, the developed contextual-based digital comic media is considered valid, practical, and effective in improving the numeracy skills of Grade II elementary school students.